An Analysis of Preschoolers’ Motor Development Based on Parenting Styles in Cukanggalih Village, Tanggerang, in 2019 - Silawati, Vivi; Yumaidah, Yuyum; Carolin, Bunga Tiara (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Preschoolers with a poor parenting style allow the possible child’s development problems to occur in the future. This study aimed at knowing the significant difference between parenting styles of parents and grandmothers’ parenting styles to preschoolers’ development at Kindergartens in Cukanggalih village. This study used a cross-sectional design. Purposive sampling technique was used with a total sample of 30 people. The instrument used in this study was a development pre-screening questionnaire (KPSP). The processing of statistical data analysis was done using an independent t-test. The finding showed that there was a significant difference between the parenting styles of parents and the grandmothers’ parenting styles against the child’s motor development. The parenting style of parents is more suitable for a child’s motor development than the grandmothers’ parenting style